Challenges of being new to Canada: considerations for physical activity. (June 2018) - Curtin, Kimberley D.; Loitz, Christina C.; Spencer-Cavaliere, Nancy; Khalema, Ernest Nene
Immigrants to Canada are less likely to be physically active compared with non-immigrants, and the interrelations between personal and environmental factors that influence physical activity for immigrants are largely unexplored. The goal of this qualitative descriptive study was to understand how the experience of being new to Canada impacts opportunities and participation in physical activity. Two focus group interviews with immigrants to Canada were conducted. The first group ( n =7) included multicultural health brokers. The second group ( n =14) included English as a second language students. Qualitative content analysis was used to determine three themes consistent with the research question: transition to Canadian life, commitments and priorities, and accessibility. Discussion was framed using a social ecological model. Implications for practice and policy are suggested including enhanced community engagement, and organizational modifications. Overall, the development and implementation of physical activity policies and practices for newcomers to Canada should be centered on newcomers' perspectives and experiences.